2020
DOI: 10.1097/psy.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Symptom Perception From a Predictive Processing Perspective: An Empirical Test Using the Thermal Grill Illusion

Abstract: Objective: In a predictive coding perspective, symptom perceptions result from an integration of pre-existing information in memory with sensory input. Physical symptoms can therefore reflect the relative predominance of either sensory input or pre-existing information. In this study, we used the thermal grill illusion (TGI), which applies interlaced warm and cool temperatures to the skin to create a paradoxical heat-pain experience. Assuming that the TGI compared to single temperature stimulation relies more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…SAEF are typically conceptualized as psychogenic in origin, and multiple models have proposed that suggestions (communications for involuntary changes in behavior and perception) contribute to the manifestation or expression of these symptoms [6]. Previous research has shown that individuals experiencing SAEF are more prone to symptoms in response to suggestions that specific (benign) stimuli will trigger symptoms [7][8][9], in a similar manner to functional neurological disorder, which is characterized by elevated direct verbal suggestibility including in response to suggestive symptom induction protocols [10,11]. The reporting of SAEF, and germane nocebo responses, such as hypochondrial concerns, is also associated with absorption [2,6], a form of dissociation that is frequently associated with suggestibility [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAEF are typically conceptualized as psychogenic in origin, and multiple models have proposed that suggestions (communications for involuntary changes in behavior and perception) contribute to the manifestation or expression of these symptoms [6]. Previous research has shown that individuals experiencing SAEF are more prone to symptoms in response to suggestions that specific (benign) stimuli will trigger symptoms [7][8][9], in a similar manner to functional neurological disorder, which is characterized by elevated direct verbal suggestibility including in response to suggestive symptom induction protocols [10,11]. The reporting of SAEF, and germane nocebo responses, such as hypochondrial concerns, is also associated with absorption [2,6], a form of dissociation that is frequently associated with suggestibility [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that individuals experiencing SAEF are more prone to symptoms in response to suggestions that specific (benign) stimuli will trigger symptoms [7][8][9], in a similar manner to functional neurological disorder, which is characterized by elevated direct verbal suggestibility including in response to suggestive symptom induction protocols [10,11]. The reporting of SAEF, and germane nocebo responses, such as hypochondrial concerns, is also associated with absorption [2,6], a form of dissociation that is frequently associated with suggestibility [9]. A role for suggestion in this condition similarly aligns with predictive processing models of SAEF, which attribute symptoms to the overweighting of precise symptom priors relative to sensory evidence, such as relying more on expectations pertaining to a specific environmental context or a specific cue [2].…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of predictive coding, central processing of incoming sensory information is biased by a mismatch resulting from incorrect internal expectations leading to symptom perception ( Figure 1 ). Providing empirical validation of this hypothesis has been a current effort: several studies report “symptom-like” somatic illusions that could be evoked in healthy participants by experimentally altering internal expectations (e.g., Iodice et al, 2019 ; Bräscher et al, 2020 ; Wolters et al, 2020 ). Moreover, experimentally induced symptoms are more persistent in patients with functional disorders, uncoupled from corresponding sensory input ( Bogaerts et al, 2010 ; Van Den Houte et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apropos, findings from empirical research by others indicate that pain experience can be predicted in Bayesian terms [ 7 ]. Furthermore, findings from empirical research by others have indicated that symptoms can reflect the relative predominance of either prior beliefs or sensory inputs with predictive processing being influenced by personal characteristics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%